Development and feasibility testing of the Pediatric Emergency Discharge Interaction Coding Scheme. (12th January 2017) - Curran, Janet A.; Taylor, Alexandra; Chorney, Jill; Porter, Stephen; Murphy, Andrea; MacPhee, Shannon; Bishop, Andrea; Haworth, Rebecca
Abstract: Background: Discharge communication is an important aspect of high‐quality emergency care. This study addresses the gap in knowledge on how to describe discharge communication in a paediatric emergency department (ED). Objective: The objective of this feasibility study was to develop and test a coding scheme to characterize discharge communication between health‐care providers (HCPs) and caregivers who visit the ED with their children. Design: The Pediatric Emergency Discharge Interaction Coding Scheme (PEDICS) and coding manual were developed following a review of the literature and an iterative refinement process involving HCP observations, inter‐rater assessments and team consensus. Setting and participants: The coding scheme was pilot‐tested through observations of HCPs across a range of shifts in one urban paediatric ED. Main variables studied: Overall, 329 patient observations were carried out across 50 observational shifts. Inter‐rater reliability was evaluated in 16% of the observations. The final version of the PEDICS contained 41 communication elements. Results: Kappa scores were greater than .60 for the majority of communication elements. The most frequently observed communication elements were under the Introduction node and the least frequently observed were under the Social Concerns node. HCPs initiated the majority of the communication. Conclusion: Pediatric Emergency Discharge Interaction Coding Scheme addresses an important gap in the discharge communication literature. The tool is useful for mapping patterns of discharge communication between HCPs and caregivers. Results from our pilot test identified deficits in specific areas of discharge communication that could impact adherence to discharge instructions. The PEDICS would benefit from further testing with a different sample of HCPs.